Poly-β-hydroxybutyrate production by Synechocystis MT_a24 in a raceway pond using urban wastewater - Grivalský, Tomáš; Lakatos, Gergely Ernő; Štěrbová, Karolína; Manoel, João Artur Câmara; Beloša, Romana; Divoká, Petra; Kopp, Julian; Kriechbaum, Ricarda; Spadiut, Oliver; Zwirzitz, Alexander; Trenzinger, Kevin; Masojídek, Jiří (Applied microbiology and biotechnology, 2024)
Poly-β-hydroxybutyrate (PHB) is a potential source of biodegradable plastics that are environmentally friendly due to their complete degradation to water and carbon dioxide. This study aimed to investigate PHB production in the cyanobacterium Synechocystis sp. PCC6714 MT_a24 in an outdoor bioreactor using urban wastewater as a sole nutrient source. The culture was grown in a thin-layer raceway pond with a working volume of 100 L, reaching a biomass density of up to 3.5 g L-1 of cell dry weight (CDW). The maximum PHB content was found under nutrient-limiting conditions in the late stationary phase, reaching 23.7 ± 2.2% PHB per CDW. These data are one of the highest reported for photosynthetic production of PHB by cyanobacteria, moreover using urban wastewater in pilot-scale cultivation which multiplies the potential of sustainable cultivation approaches. Contamination by grazers (Poterioochromonas malhamensis) was managed by culturing Synechocystis in a highly alkaline environment (pH about 10.5) which did not significantly affect the culture growth. Furthermore, the strain MT_a24 showed significant wastewater nutrient remediation removing about 72% of nitrogen and 67% of phosphorus. These trials demonstrate that the photosynthetic production of PHB by Synechocystis sp. PCC6714 MT_a24 in the outdoor thin-layer bioreactor using urban wastewater and ambient carbon dioxide. It shows a promising approach for the cost-effective and sustainable production of biodegradable carbon-negative plastics. KEY POINTS: • High PHB production by cyanobacteria in outdoor raceway pond • Urban wastewater used as a sole source of nutrients for phototrophic growth • Potential for cost-effective and sustainable production of biodegradable plastics.
Keywords: Carbon Dioxide; Polyesters; Ponds; hydroxybutyráty; Polyhydroxybutyrate; Raceway pond cultivation; Synechocystis; Urban wastewater; polyestery; odpadní voda; biologicky odbouratelné plasty; Wastewater; Hydroxybutyrates; rybníky; Biodegradable Plastics; Biodegradable plastics; oxid uhličitý